Dominance Of Market Share Of Sukuk In Indonesia - Selasi, Dini (Syntax Literate, 2020)
Indonesia is one of the issuers of sukuk in the world with various series that have been issued, this sukuk aims to help finance the state budget for various sectors for sustainable development programs. This study uses a qualitative research method using a phenomenological approach. The results show that the government is still dominated by sukuk because most of the financing of sukuk in Indonesia are government projects in various sectors, in their issuance in collaboration with conventional and sharia banking, securities companies that become AB Bursa. Sukuk series issued by the government such as Islamic Fixed Rate (IFR), greensukuk, Indonesian hajj fund sukuk (SDHI), savings sukuk, retail sukuk, sharia state treasury bills (SPNS), project based sukuk (PBS).